Transcription Expression and Clinical Significance of Dishevelled-3 mRNA and δ-Catenin mRNA in Pleural Effusions from Patients with Lung Cancer - Xiao-Yan Li; Shu-Li Liu; Na Cha; Yu-Jie Zhao; Shao-Cheng Wang; Wei-Nan Li; En-Hua Wang; Guang-Ping Wu (Clinical and Developmental Immunology)
Objective. To evaluate diagnostic utility of Dishevelled-3 (DVL-3) mRNA and δ-catenin mRNA expression in pleural effusions of patients with lung cancer. Methods. DVL-3 mRNA and δ-catenin mRNA levels were assessed by performing RT-PCR on pleural effusion specimens from patients with lung cancer (n=75) and with lung benign disease (n=51). Results. The expressions of DVL-3 mRNA and δ-catenin mRNA were significantly higher in malignant than in benign lung disease (P<0.01) and were obviously higher than cytology in adenocarcinoma (P<0.01). In single use, DVL-3 mRNA had the highest specificity (94.1%) and PPV (95.7%), whereas δ-catenin mRNA had the highest sensitivity (92.0%) and NPV (88.5%). When combinations of markers were evaluated together, DVL-3 mRNA and δ-catenin mRNA gave a high-diagnostic performance: sensitivity of 100.0%, NPV of 100.0%, and accuracy of 96.0%, respectively. Conclusion. As molecular markers of detecting pleural micrometastasis, DVL-3 mRNA and δ-catenin mRNA are helpful to diagnose the cancer cells in pleural effusions of patients with lung cancer.